An overview of the applications of furfural and its derivatives - Eseyin, Anthonia, E.; Steele, Philip, H. (International Journal of Advanced Chemistry, 2015)
Recently, furfural, â€œthe sleeping beauty bio-renewable chemicalâ€ has gained a renewed attention as a potential chemical for the production of biofuels and biochemicals. Furfural is the most commonly produced industrial chemical because its production is very flexible. It is one of the top value-added chemicals that can be produced from biomass. Furfural and its derivatives have been extensively used in plastics, pharmaceutical and agrochemical industries. Furfural is a natural precursor to a range of furan-based chemicals and solvents such as dihydropyran, methyltetrahydrofuran, tetrahydrofuran, methylfuranfurfuryl alcohol, tetrahydrofurfuryl alcohol and furoic acid. Furfural and its derivatives have been widely applied as fungicides and nematicides, transportation fuels, gasoline additives, lubricants, resins, decolorizing agents, jet fuel blend stocks, drugs, insecticides, bio-plastics, flavor enhancers for food and drinks, rapid all-weather repair system for bomb-damaged runways and pot holes and also for wood modification and book preservation.